Peningkatan Keterampilan Bernyanyi Vokal Solo Menggunakan Metode Imitasi Bagi Siswa Kelas VIII di SMP Pertiwi 2 Padang - Niko, Niko Siregar; Jagar Lumbantoruan (Universitas Negeri Padang, 2024)
This research aims to describe the process of the imitation method to improve solo vocal singing skills for class VIII students at SMP Pertiwi 2 Padang. This research is qualitative research that uses the imitation method. The instrument for this research was the researcher himself and was assisted by supporting instruments such as writing instruments, piano instruments. Data collection techniques are carried out through observation, interviews, documentation, literature study. Data analysis techniques are collecting data, classifying data, clarifying data, analyzing data, describing and concluding. The problem formulated in this research is whether using the imitation method can improve students' singing skills in solo vocal singing. This type of Classroom Action Research (PTK) consists of two cycles. Each cycle includes the stages of planning, implementation, observation, evaluation, reflection. The research results showed that the use of the imitation method showed positive results from the first cycle and the second cycle was carried out optimally. The results of the research and discussion can be concluded that there is an increase in solo vocal singing skills through the imitation method, which was obtained from a total of 27 students who obtained an average score in the pre-cycle of 56% in the poor category because there were still many students who did not understand how to apply solo vocal singing using Correct. In cycle I, the students' average score was 64% compared to the average score in the pre-cycle, there was no significant increase because many did not understand how to apply solo vocal singing techniques. In the cycle where the students' average score was 81% in this cycle, it was seen that they had improved significantly, in the solo vocal singing technique the students also applied it correctly and improved the students' singing abilities.